A Brief Report on Teacher Mask Wearing and Learning in Children with ASD - Heisler, Makayla; Mattson, Jennifer Gillis; Cavalari, Rachel N. S. (Journal of the American Academy of Special Education Professionals, 2024)
There is a rich literature on effective instructional practices for children with Autism Spectrum Disorder (ASD). When some schools resumed in-person instruction during the COVID-19 pandemic, mask wearing was required by teachers, therapists, and students. Given limited literature on the importance of attending to the mouth during interactions for children with ASD, it was unclear if wearing a mask that covered the mouth would impact learning. A brief systematic assessment was conducted to examine the impact of a mask on learning in four children with ASD. Results showed that mask wearing did not appear to impact learning.